P-doped carbon layer coated graphite felt fiber core-shell structure electrode material and preparation method and application thereof

By introducing P doping into the graphite felt fiber electrode and forming a carbon layer, the problem of insufficient activity of electrode materials in organic flow batteries is solved, and the performance of purple-sine-based water-based organic flow batteries is significantly improved, achieving higher electricity Chemical activity and stability.

CN119170789APending Publication Date: 2024-12-20LIAONING UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311663414.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-06
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The electrode materials of existing water-based redox flow batteries have poor electrochemical reaction activity in organic flow batteries. Due to the significant differences between inorganic and organic electroactive ions, the previous research results have limited effect on improving the performance of organic battery systems, which is limited. The development of AORFBs.

Method used

The graphite felt fiber core-shell structure electrode material coated with P-doped carbon layer is prepared by physical impregnation and heat treatment. By introducing P elements into the graphite felt, a nano-thick carbon layer is generated to enhance the electrode's electron conductivity and purple essence. The adsorption properties of molecules are suitable for purple-sine-based water-based organic liquid flow batteries.

Benefits of technology

It significantly improves the voltage efficiency, energy efficiency and peak power density of the purple-sine-based water-based organic liquid flow battery, enhances the cyclic stability and capacity retention rate of the battery, reduces the overpotential, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170789A_ABST
    Figure CN119170789A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials and energy storage, and particularly relates to a P-doped carbon layer coated graphite felt fiber core-shell structure electrode material and a preparation method and application thereof. Soaking the graphite felt in ethanol, performing ultrasonic cleaning, and drying; soaking in a precursor aqueous solution containing a carbon and phosphorus source, and carrying out ultrasonic treatment and vacuum drying; and carrying out high-temperature heat treatment, cooling, washing, and carrying out vacuum drying to obtain the P-doped carbon layer coated graphite felt fiber core-shell structure electrode material P-C (at) GF. Under the current density of 60mA. Cm <-2 >, the voltage efficiency VE and the energy efficiency EE of the viologen-based aqueous organic flow battery taking the P-C-GF as the anode are respectively 5.34% and 6.18% higher than those of a battery taking blank GF as an electrode; after 100 times of charge and discharge cycles, the capacity retention ratio is increased by about 20%, and the peak power density is increased by about 40%. The method disclosed by the invention is simple, green and efficient, and has a good application prospect in the aqueous organic flow battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials and energy storage, and specifically relates to a graphite felt fiber core-shell structure electrode material coated with a P-doped carbon layer, and a preparation method and application thereof. Background Art

[0002] Traditional aqueous redox flow batteries (ARFBs) based on inorganic metal electroactive ions have problems such as limited resources, low energy density and high cost. All-vanadium redox flow batteries are currently the most widely studied aqueous flow batteries that have entered the commercial stage, but the limitation of vanadium mineral resources and high cost are important reasons that restrict its development. In recent years, aqueous organic flow batteries (AORFBs) with water-soluble organic electroactive substances as active electrolytes have received increasing attention. Organic electrolyte materials have inherent advantages such as diverse molecular structures, adjustable redox potentials, low costs, and wide sources, making AORFBs an important direction for the development of flow batteries in the future. In addition, in aqueous organic redox flow batteries, viologen molecules have become the most promising anode active electrolytes in AORFBs due to their excellent electrochemical redox reversibility, high water solubility and easy synthesis. Generally, viologen derivatives can undergo two single-electron redox reactions, which can provide batteries with higher energy density.

[0003] Electrode materials, as the place where electrochemical reactions occur, are one of the most critical components in flow batteries. Electrodes not only provide channels for electrolyte transfer, but also provide active sites for their electrochemical redox reactions. At present, carbon fiber-based porous materials, such as graphite felt and carbon felt, have the advantages of good conductivity, large specific surface area, good stability, high mechanical strength, and low price, and have become the most widely used and best-performing electrode materials in flow batteries. However, the electrochemical reaction activity of such materials themselves is poor, and effective modification is required to obtain better battery performance. In addition, different electrochemical reactions have very different requirements for the surface properties of electrode materials. Therefore, for a specific electrochemical reaction system, designing electrode materials with specific surface composition and structure is the fundamental way to improve the performance of the corresponding battery. At present, the surface modification methods of electrode materials mainly include surface etching, catalyst modification, and heteroatom doping. Among them, through appropriate surface modification treatment, the reaction activity, reaction area, and electronic conductivity of the electrode material can be comprehensively regulated to obtain an electrode material with the best match to the corresponding battery system. However, there are few studies on electrode materials for organic flow batteries, and because the electrode reaction kinetics of organic active molecules are significantly different from those of inorganic metal ions, which are more studied, the previous research results may not have advantages for the electrochemical reaction performance in organic battery systems. Therefore, it is necessary to design more suitable electrode materials based on the electrochemical reaction characteristics of specific organic electroactive molecules to further improve the performance of AORFBs and promote their industrial development. Summary of the invention

[0004] In order to solve the above key problems, the present invention adopts a simple physical impregnation and heat treatment process to prepare a P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material, which shows very excellent electrochemical activity for viologen derivatives and can effectively improve the performance of viologen-based aqueous organic liquid flow batteries.

[0005] To achieve the above object, the technical solution adopted by the present invention is: a graphite felt fiber core-shell structure electrode material coated with a P-doped carbon layer, the preparation method of which comprises the following steps:

[0006] 1) Soaking the graphite felt GF in ethanol, cleaning it in an ultrasonic bath to remove surface impurities, and drying the cleaned graphite felt GF;

[0007] 2) immersing the pretreated graphite felt GF electrode in an aqueous solution of a precursor containing a carbon and phosphorus source, ultrasonicating, taking out the completely soaked graphite felt GF, and vacuum drying;

[0008] 3) The dried electrode is subjected to high-temperature heat treatment, washed after cooling, and vacuum dried to obtain a P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material PC@GF.

[0009] Preferably, in the above-mentioned P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material, in step 1), the diameter of the carbon fiber in the graphite felt GF is 2um to 15um, the porosity is 60% to 90%, and the apparent density is 0.1 to 0.2g / cm 3 , resistivity 1~5Ω·mm.

[0010] Preferably, in the above-mentioned P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material, in step 1), the drying is carried out in a vacuum drying oven at 60° C. to 80° C.

[0011] Preferably, in the above-mentioned P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material, in step 2), the precursor of the carbon-phosphorus source includes but is not limited to 1-hydroxyethyl diphosphonic acid, and its concentration in the aqueous solution is 1wt% to 10wt%.

[0012] Preferably, in the above-mentioned P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material, in step 2), the vacuum drying temperature is 60°C to 80°C.

[0013] Preferably, in the above-mentioned P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material, in step 3), the high-temperature heat treatment conditions are calcination at 900-1300°C for 1h-5h in a nitrogen or argon atmosphere, and a heating rate of 2-5°C / min.

[0014] Preferably, in the above-mentioned P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material, in step 3), the washing is performed with a mixed solution of equal volumes of ethanol and water.

[0015] The application of the above-mentioned P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material in viologen-based aqueous organic liquid flow battery.

[0016] Preferably, the above-mentioned P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material is used in a viologen-based aqueous organic liquid flow battery, with the above-mentioned PC@GF electrode material as the working electrode, the platinum wire electrode as the auxiliary electrode, and the silver / silver chloride electrode Ag / AgCl as the reference electrode. In the viologen-based aqueous organic liquid flow battery, the supporting electrolyte in the anode electrolyte is potassium chloride or sodium chloride; and the active electrolyte is a water-soluble viologen derivative.

[0017] Preferably, in the application of the above-mentioned P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material in a viologen-based aqueous organic liquid flow battery, the concentration of potassium chloride or sodium chloride is 0.5 mol / L to 2 mol / L, and the concentration of the water-soluble viologen derivative is 0.05 mol / L to 1 mol / L.

[0018] The present invention adopts a simple physical impregnation and heat treatment process to prepare a new type of P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material PC@GF, which can be used as the anode electrode material of viologen-based aqueous organic liquid flow battery to significantly improve the battery performance. Using 1-hydroxyethyl diphosphonic acid as the carbon-containing P source, the graphite felt GF is completely immersed in its aqueous solution, dried and then heat-treated. The thermal decomposition reaction of 1-hydroxyethyl diphosphonic acid is used to in-situ generate a nanometer-thick P-containing thin carbon layer on the surface of the carbon fiber; the carbon layer has both excellent electronic conductivity and good adsorption performance for viologen molecules, and therefore shows excellent electrochemical performance for viologen electrolyte. The viologen-based aqueous organic liquid flow battery with the prepared PC@GF as the anode has a high conductivity at 60 mA·cm -2 At a current density of , the voltage efficiency VE and energy efficiency EE are 5.34% and 6.18% higher than those of the battery with blank GF as electrode, respectively; after 100 charge and discharge cycles, the capacity retention rate is about 20% higher, and the peak power density is increased by about 40%. The method of the present invention is simple, green and efficient, and has good application prospects in aqueous organic liquid flow batteries.

[0019] The beneficial effects of the present invention are:

[0020] 1. The present invention uses commercial graphite felt as the basic raw material, and can prepare a new type of P atom-doped carbon layer-coated graphite felt fiber core-shell structure electrode material through a simple physical impregnation and heat treatment process. The method is simple, efficient, low-cost, and suitable for large-scale production.

[0021] 2. The PC@GF electrode material prepared by the present invention has both excellent electronic conductivity and electrochemical activity, and shows excellent electrochemical reaction performance for viologen derivatives.

[0022] 3. The viologen-based aqueous organic flow battery with PC@GF as the anode shows lower overpotential, higher battery efficiency and power density than the battery with blank graphite felt as the electrode.

[0023] 4. Due to the use of highly active electrode materials, the electrochemical oxidation reaction rate of reduced viologen is increased, and accordingly, its chemical oxidation by dissolved oxygen in water is weakened, so that the corresponding battery has better capacity retention and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Scanning electron microscope images of GF electrode (a) and PC@GF electrode (b) and EDS mapping of PC@GF (c).

[0025] Figure 2 High-resolution transmission electron microscopy images of GF electrode (a) and PC@GF electrode (b).

[0026] Figure 3 This is a CV comparison diagram of PC@GF electrode and GF electrode in 2.5mM BTMAP-vi+1M NaCl anolyte.

[0027] Figure 4 This is a schematic diagram of the working principle of a neutral aqueous organic redox flow battery.

[0028] Figure 5 BTMAP-vi / N with GF and PC@GF as electrodes, respectively me -The rate performance diagram (a) and cycle performance diagram (b) of TEMPO aqueous organic flow battery. Specific implementation methods

[0030] In order to enable those skilled in the art to better understand the technical solution of the present invention, it is described in detail below with reference to the accompanying drawings and embodiments.

[0031] Example 1 Preparation of graphite felt fiber core-shell structure electrode material coated with P-doped carbon layer

[0032] A P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material was prepared by a simple physical impregnation and heat treatment process. The preparation method includes the following steps:

[0033] 1) Soak the graphite felt in ethanol and clean it in an ultrasonic bath for 10 minutes to remove surface impurities. Then put the cleaned GF into a vacuum drying oven and dry it at 60°C overnight.

[0034] 2) The GF electrode pretreated in step 1) was immersed in a 1.7 wt % aqueous solution of 1-hydroxyethyl diphosphonic acid, and ultrasonicated for half an hour. The completely soaked GF was taken out and dried in a vacuum drying oven at 60° C. overnight.

[0035] 3) The electrode dried in step 2) was placed in a tube furnace and calcined at 900°C for 3h under a nitrogen atmosphere, with a heating rate of 5°C / min. After cooling, it was fully washed with a mixed solution of equal volumes of ethanol and water (ethanol: water = 1:1), and dried in a vacuum drying oven at 60°C overnight to obtain a P-doped carbon layer-coated graphite felt fiber core-shell structure electrode (PC@GF).

[0036] The electronic conductivities of the obtained pretreated GF and PC@GF electrode materials were 151.15 S cm -1 and 157.15Scm -1 .

[0037] like Figure 1The following are scanning electron microscope images of GF and PC@GF. It can be seen that the fiber diameters of GF and PC@GF are both above 10 microns. The original GF fiber surface has many defects, many grooves, and a relatively rough surface. The surface of the PC@GF electrode is smoother than that of the GF. The surface of the PC@GF seems to be covered with a thin layer of gauze. This may be because the carbon-containing P source forms a thin carbon layer on the surface of the carbon fiber during the heat treatment process and fills the grooves, making the grooves on the fiber surface fewer and shallower, and the surface tends to be smoother. In addition, the EDS element mapping of the PC@GF electrode is shown in Figure 2. Figure 1 (c) It is obvious that the surface of the PC@GF electrode is mostly carbon, and a small amount of N, O, and P can also be detected, indicating the successful introduction of P. O and P elements mostly coexist in the fiber edge defects, and these active sites may promote the electrochemical redox reaction of the viologen molecule (BTMAP-vi).

[0038] like Figure 2 The figure shows high-resolution transmission electron micrographs of GF and PC@GF carbon fibers. The original GF surface presents a relatively discontinuous graphite microcrystalline structure. After P doping, a thin carbon layer of about 10 nm is formed on the GF surface, which makes the PC@GF electrode have better conductivity and is more conducive to electron transfer. Therefore, for PC@GF, 1-hydroxyethyl diphosphonic acid may have a certain etching effect on the GF matrix, while generating a carbon layer with better crystallinity, making the groove shallower and the surface smoother. The synergistic effect of increased conductivity and active sites may be the main reason for its good electrochemical activity.

[0039] Example 2 Electrochemical performance of graphite felt fiber core-shell structure electrode material coated with P-doped carbon layer

[0040] Methods: The electrochemical performance of BTMAP-vi on different electrodes was tested using a commonly used three-electrode system. GF and PC@GF electrode materials were used as working electrodes (0.5*0.5cm 2 ), platinum wire electrode and silver / silver chloride electrode (Ag / AgCl) were used as auxiliary electrode and reference electrode, respectively. The concentration of active substance (BTMAP-vi) in anolyte was 2.5mmol / L, and the supporting electrolyte was 1mol / L NaCl. The electrochemical properties of PC@GF electrode material were studied by cyclic voltammetry (CV).

[0041] like Figure 3The figure shows the CV graphs of GF and PC@GF electrodes in 2.5mM BTMAP-vi+1M NaCl anolyte at a scan rate of 30mV / s. It can be seen that two pairs of redox peaks appear on the surface of both GF and PC@GF electrodes, corresponding to the two single-electron electrochemical redox processes of BTMAP-vi. Among them, compared with the original GF electrode, the redox peak current of the PC@GF electrode is the highest and the reversibility is also very good. This shows that the PC@GF electrode has a better electrochemical activity.

[0042] Example 3 Battery performance of a new type of P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material

[0043] Methods: Assembly of 0.1M BTMAP-vi / N me -TEMPO full cell, to investigate the practical application performance of GF and PC@GF electrodes in viologen-based AORFB. 2 GF or PC@GF electrodes were used as positive and negative electrodes. DSV anion exchange membrane was selected as the diaphragm. The anolyte was 10 mL 0.1 mol / L BTMAP-vi, and the catholyte was 20 mL 0.1 mol / L N me -TEMPO. The supporting electrolyte is 1mol / L NaCl solution. The charge and discharge performance of the combined battery is systematically tested. The reservoir is purged with nitrogen to replace the O2 in the electrolyte. 0.1mol / L BTMAP-vi / N me -TEMPO AORFB has a charge and discharge cut-off voltage of 0.1V to 2.3V and a current density of 60mA cm -2 、80mA cm -2 and 100mA cm -2 , at 60mA cm -2 The GF and PC@GF electrodes were cycled for 100 cycles in 0.1M BTMAP-vi / N me -Charge and discharge cycle performance on TEMPO AORFB.

[0044] like Figure 4 The figure shows the working principle of the neutral aqueous organic redox flow battery. The anode electrolyte is 10mL 0.1M BTMAP-vi+1M NaCl, and the cathode electrolyte is 20mL 0.1MN me -TEMPO+1M NaCl, the electrolyte flow rate was controlled at 36 mL / min by a peristaltic pump, GF and PC@GF electrodes were the positive and negative electrodes, and the diaphragm was a DSV anion exchange membrane.

[0045] like Figure 5 As shown, Figure 5(a) shows the battery efficiency and discharge capacity of GF and PC@GF electrodes at different current densities. The coulombic efficiency (CE) of the two AORFBs is similar, both close to 100%. With the increase of current density, the voltage efficiency (VE) and energy efficiency (EE) of both gradually decrease. At different current densities, the polarization overpotential of the PC@GF electrode is lower and the discharge capacity is higher. Among them, the BTMAP-vi / N with PC@GF as electrode me -TEMPO AORFB at a current density of 60 mA cm -2 The VE and EE of the AORFB with PC@GF as electrode are 5.34% and 6.18% higher than those of the battery with GF as electrode, respectively. At all current densities, the VE and EE of the AORFB with PC@GF as electrode are higher than those of the battery with GF electrode, and the gap between the two batteries becomes larger with the increase of current density. This further indicates that the rate capability of the PC@GF battery has been improved. Figure 5 (b) The current density of the two batteries is 60 mA cm -2 The discharge capacity and efficiency after 100 charge and discharge cycles are shown in Figure 2. The capacity retention rate of the GF battery is 51.16%, while that of the PC@GF battery is 70%, further indicating that the PC@GF battery has better stability.

Claims

1. A graphite felt fiber core-shell structure electrode material coated with a P-doped carbon layer, characterized in that: The preparation method comprises the following steps: 1) Soaking the graphite felt GF in ethanol, cleaning it in an ultrasonic bath to remove surface impurities, and drying the cleaned graphite felt GF; 2) immersing the pretreated graphite felt GF electrode in an aqueous solution of a precursor containing a carbon and phosphorus source, ultrasonicating, taking out the completely soaked graphite felt GF, and vacuum drying; 3) The dried electrode is subjected to high-temperature heat treatment, washed after cooling, and vacuum dried to obtain a P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material PC@GF.

2. The P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material according to claim 1, characterized in that: In step 1), the diameter of the carbon fiber in the graphite felt GF is 2um to 15um, the porosity is 60% to 90%, and the apparent density is 0.1 to 0.2g / cm 3 , resistivity 1~5Ω·mm.

3. The P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material according to claim 1, characterized in that: In step 1), the drying is carried out in a vacuum drying oven at 60°C to 80°C.

4. The P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material according to claim 1, characterized in that: In step 2), the precursor containing the carbon-phosphorus source includes but is not limited to 1-hydroxyethyl diphosphonic acid, and its concentration in the aqueous solution is 1 wt% to 10 wt%.

5. The P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material according to claim 1, characterized in that: In step 2), the vacuum drying temperature is 60°C to 80°C.

6. The P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material according to claim 1, characterized in that: In step 3), the high temperature heat treatment conditions are calcination at 900-1300° C. for 1 h to 5 h in a nitrogen or argon atmosphere, with a heating rate of 2-5° C. / min.

7. The P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material according to claim 1, characterized in that: In step 3), the washing is performed with a mixed solution of equal volumes of ethanol and water.

8. Use of a graphite felt fiber core-shell structure electrode material coated with a P-doped carbon layer as described in any one of claims 1 to 7 in a viologen-based aqueous organic liquid flow battery.

9. The use of a P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material in a viologen-based aqueous organic flow battery according to claim 8, characterized in that: The PC@GF electrode material according to claim 1 is used as a working electrode, a platinum wire electrode is used as an auxiliary electrode, and a silver / silver chloride electrode Ag / AgCl is used as a reference electrode. In the viologen-based aqueous organic liquid flow battery, the supporting electrolyte in the anode electrolyte is potassium chloride or sodium chloride; and the active electrolyte is a water-soluble viologen derivative.

10. The use of a P-doped carbon layer-coated graphite felt fiber core-shell structure electrode material in a viologen-based aqueous organic liquid flow battery according to claim 9, characterized in that: The concentration of potassium chloride or sodium chloride is 0.5 mol / L to 2 mol / L, and the concentration of the water-soluble viologen derivative is 0.05 mol / L to 1 mol / L.

Citation Information

Cited By

  • Organic polycyclic phosphorus-containing micromolecule doped electrode material and preparation method and application thereof

    CN122511918A